Kinematics of side and cross circles on pommel horse - Fujihara, T.; Gervais, P. (European Journal of Sport Science, 2010)
One of the most fundamental skills on the pommel horse is double leg circles (circles). Circles can be performed on all parts of the pommel horse. It was hypothesized that the different sets of physical constraints of the apparatus require a gymnast to adapt circles technique. The purpose of this study was to quantify how gymnasts modify their technique during circles to accommodate different physical obstacles due to different support surfaces and body orientations. To investigate these adaptations, a comparison of the two most common circles on pommel horse - namely, circles in cross support (cross-circles) and circles in side support (side-circles) - was carried out. Seven elite male gymnasts performed three sets of 10 cross-circles and side-circles on a pommel horse. Three-dimensional coordinates were acquired using 12 Qualisys ProReflex motion tracking cameras operating at 120 Hz. Temporal characteristics, the motion of the centre of mass, and the body angles - flexion and lateral flexion - were analysed. We found that cross-circles took less time to complete a single circle (0.92±0.02 vs. 0.95±0.02 s), had a smaller ratio for the rear support phase (0.15±0.02 vs. 0.18±0.03), a narrower supporting-hand distance (0.33±0.03 vs. 0.52±0.00 m), greater flexion of the body over the rear support phase (44±12° vs. 27±8°), and less lateral flexion of the body over the single-hand support phase (entry: 20±5° vs. 35±3°; exit: 26±4° vs. 33±4°) than side-circles. Our results suggest that gymnasts adapt their technique to the physical constraints imposed by the shape of the pommel horse and the location and orientation of the circles. Cross-circles were characterized by a high rear support position with a narrower hand-spacing, which would require excellent shoulder flexibility and strength. Consequently, lack of these traits may explain the need for greater body flexion in cross-circles than in side-circles during rear support. Understanding the technical differences will facilitate an effective transfer of the technical similarities among different types of circles.